2018
DOI: 10.1101/474064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term population studies uncover the genome structure and genetic basis of xenobiotic and host plant adaptation in the herbivoreTetranychus urticae

Abstract: Pesticide resistance arises rapidly in arthropod herbivores, as can host plant adaptation, and both are significant problems in agriculture. These traits have been challenging to study as both are often polygenic and many arthropods are genetically intractable. Here, we examined the genetic architecture of pesticide resistance and host plant adaptation in the two-spotted spider mite, Tetranychus urticae, a global agricultural pest. We show that the short generation time and high fecundity of T. urticae can be … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 74 publications
0
62
0
Order By: Relevance
“…None of the QTLs was associated with the CCE04 locus (located on pseudochromosome 1 at 2.39 Mb), but contained other interesting candidate genes: ACCase -the target of keto-enol acaricides (on pseudochromosome 1 at 6.56 Mb), a region containing P450s (on pseudochromosome 1 at 24.13 Mb) belonging to the same P450 subfamily as CYP392E10, known to metabolize spirodiclofen 11 and cytochrome P450 reductase (CPR) (on pseudochromosome 2 at 5.69 Mb). 12 On the other hand, it is still possible that these genomic loci harbor regulators (e.g. transcription factors) that are associated with the potentially fixed CCE04 SR-VP allele.…”
Section: Discussionmentioning
confidence: 99%
“…None of the QTLs was associated with the CCE04 locus (located on pseudochromosome 1 at 2.39 Mb), but contained other interesting candidate genes: ACCase -the target of keto-enol acaricides (on pseudochromosome 1 at 6.56 Mb), a region containing P450s (on pseudochromosome 1 at 24.13 Mb) belonging to the same P450 subfamily as CYP392E10, known to metabolize spirodiclofen 11 and cytochrome P450 reductase (CPR) (on pseudochromosome 2 at 5.69 Mb). 12 On the other hand, it is still possible that these genomic loci harbor regulators (e.g. transcription factors) that are associated with the potentially fixed CCE04 SR-VP allele.…”
Section: Discussionmentioning
confidence: 99%
“…The application of acaricides still remains the most frequently used method to keep T. urticae populations below economic thresholds for many crops. However, the fast development of resistance in the species, in part due to biological characteristics such as a short life cycle, high reproductive potential, arrhenotokous reproduction, together with a broad host plant range, reduces the efficacy of the application of acaricides (Dermauw et al 2013;Van Leeuwen et al 2010;Wybouw et al 2019). It is therefore important to continue to develop acaricides with new modes of action and limited cross-resistance to other commercially available compounds to secure proper resistance management in T. urticae (Nauen et al 2012;Van Leeuwen, Thomas et al 2015;Fotoukkiaii et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For spider mites, it has been shown that detoxification enzymes such as cytochrome P450 monooxygenases (P450s) are involved in spirodiclofen resistance, while carboxyl/choline esterases (CCEs) are much likely involved in sequestration of spirodiclofen (Demaeght et al, 2013;Kramer & Nauen, 2011;Wei et al, 2019, Bajda et al 2015. In a recent study, spirodiclofen resistance in T. urticae was also mapped to a number of genomic loci (Quantitative Trait Loci (QTL) mapping), with one of the QTLs containing the gene encoding ACCase, the target-site of spirodiclofen (Wybouw et al, 2019). In the ACCase gene of the resistant strain that was used for the mapping experiment, a non-synonymous mutation, A1079T, was also identified.…”
Section: Several Chemical Classes Of Acaricides With Different Modes mentioning
confidence: 99%
“…In the ACCase gene of the resistant strain that was used for the mapping experiment, a non-synonymous mutation, A1079T, was also identified. This mutation, however, was located outside the CTdomain of ACCase and awaits functional validation (Khajehali, 2010;Wybouw et al, 2019).…”
Section: Several Chemical Classes Of Acaricides With Different Modes mentioning
confidence: 99%